The creative behavior of virtual idol fans: a psychological perspective based on MOA theory - Wang, Qingnian; Long, Shuyu; Zeng, Yanfei; Tang, Lan; Wang, Yunpei (Frontiers in Psychology, 2023)
Breakthroughs in digital technology are accelerating the development and commercialization of virtual idols. They are overturning the traditional one-way communication between idols and fans, turning fans into producers and consumers. Therefore, identifying the motivations for fan creation can regulate and guide the creative behavior of fans and turn their creativity into productivity. This paper took "the factors influencing fans' spontaneous participation in creating virtual idols" as the primary research question, took the Motivation Opportunity Ability (MOA) theory as the research framework, used questionnaires as the primary research method, and combined the relevant research on motivation theory and self-determination theory to explore fans' creative behavior from the psychological perspective in depth. The empirical tests revealed that in the motivation dimension, interest motivation, achievement motivation, social motivation, and utility motivation all positively influenced fans' creative behavior; in the opportunity dimension, fans' perceived cost had a significant negative moderating effect on the influence of interest motivation, social motivation, and utility motivation on fans' creative behavior; fans' perceived community atmosphere was substantial. The moderating effect of knowledge and skills on the capability dimension was insignificant. For the virtual idol industry, the future development of the industry could not only focus on IP image creation and content production but also effectively stimulate fans' creative motivation through the creation of an excellent community atmosphere, the provision of targeted creator services, and the reduction of fans' perceived costs in the creation process.